The Concept of Jihad from the Perspective of Pesantren - Azizah, Balkis; Ridla, Hadziq Zubad (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2024)
Jihad and pesantren are two things that have a connection, especially seeing the many phenomena that occur that lead to pesantren institutions. The purpose of this research is to find out the concept of pesantren-style jihad. Researchers used qualitative methods with the type of field research. Researchers used primary data sources as basic data obtained from analyzing phenomena and secondary data in books, journals, theses, and online and physically relevant to the research. In conducting research, researchers use documentation techniques as data collection techniques. The study's results explained that jihad has many versions, meanings, and perspectives. Still, the explanation that has been explained provides a conceptual description of pesantren-style jihad, namely patience in facing trials (Ali Imran: 142), maintaining the identity of the Muslim personality (Al-'Ankabut: 6), and the ability to restrain lust (Q.S At-Taubah: 79). It was also found that pesantren can be an alternative in facing the challenges of globalization that refer to juvenile delinquency by becoming a workshop for character cultivation. In addition, pesantren alums can be a reference in the environment to answer globalization problems based on a moderate mindset between religion and the state.